The influence of habitual protein intake in early childhood on BMI and age at adiposity rebound: results from the DONALD Study - Günther, A L B; Buyken, Anette; Kroke, A (International Journal of Obesity)

REVIS – Reform der Ernährungs- und Verbraucherbildung in Schulen - Schlegel-Matthies, Kirsten (Haushalt & Bildung)

Zur Analyse von Unterrichtsmaterialien für die Ernährungs- und Verbraucherbildung - Methfessel, B.; Schlegel-Matthies, Kirsten (Haushalt & Bildung)

A fast k-means implementation using coresets - Frahling, Gereon; Sohler, Christian (Proceedings of the twenty-second annual symposium on Computational geometry - SCG '06)
In this paper we develop an efficient implementation for a k-means clustering algorithm. Our algorithm is a variant of KMHybrid [28, 20], i.e. it uses a combination of Lloyd-steps and random swaps, but as a novel feature it uses coresets to speed up the algorithm. A coreset is a small weighted set of points that approximates the original point set with respect to the considered problem. The main strength of the algorithm is that it can quickly determine clusterings of the same point set for many values of k. This is necessary in many applications, since, typically, one does not know a good value for k in advance. Once we have clusterings for many different values of k we can determine a good choice of k using a quality measure of clusterings that is independent of k, for example the average silhouette coefficient. The average silhouette coefficient can be approximated using coresets.To evaluate the performance of our algorithm we compare it with algorithm KMHybrid [28] on typical 3D data sets for an image compression application and on artificially created instances. Our data sets consist of 300,000 to 4.9 million points. We show that our algorithm significantly outperforms KMHybrid on most of these input instances. Additionally, the quality of the solutions computed by our algorithm deviates less than that of KMHybrid.We also computed clusterings and approximate average silhouette coefficient for k=1,…,100 for our input instances and discuss the performance of our algorithm in detail.

Design and Construction of a 3D-Scanning-Laservibrometer - Becker, C; Wedman, S; Hemsel, Tobias (Proceedings of 2nd International Workshop on Piezoelectric Materials and Applications in Actuators)

Interaktive 3D-Visualisierung multidimensionaler Datensätze - Lindner, M.; Goetz, F.; Weise, R.; Fricke, H.; Burchert, W.; Domik, Gitta

Pizza, Pasta und Döner Kebab: Mediterranean Dishes in the Everyday Life of German Young People - Bartsch, Silke; Methfessel, Barbara; Schlegel-Matthies, Kirsten (Mediterranean Food. Concepts and Trends. Proceedings of the 15th International Ethnological Food Research Conference, Dubrovnik, 27 September - 3 October)

Pizza, Pasta, Döner Kebab - Mittelmeerkost im Alltag deutscher Jugendlicher. Historische und soziale Hintergründe - Schlegel-Matthies, Kirsten; Methfessel, Barbara; Bartsch, Silke (Haushalt & Bildung)

Mittelmeerkost im Alltag deutscher Jugendlicher - Ein Lehr-Forschungsprojekt mit Studierenden in Heidelberg und Paderborn - Schlegel-Matthies, Kirsten; Methfessel, Barbara (Haushalt & Bildung)

Zur Entwicklung eines Kerncurriculums für den Lernbereich „Arbeitslehre" - Philipps, U.; Bigga, Regine (Haushalt & Bildung)

Dynamische Kantenextraktion: Ein Verfahren zur Generierung von Tracking-Informationen für Augmented Reality-Anwendungen auf Basis von 3D-Referenzmodellen - Matysczok, Carsten

Glycaemic index and glycaemic load in the diet of healthy schoolchildren: trends from 1990 to 2002, contribution of different carbohydrate sources and relationships to dietary quality. - Buyken, Anette; Dettmann, W; Kersting, M; Kroke, A (Br J Nutr)

Glycaemic index of potatoes: myth and reality from a European perspective - Buyken, Anette; Kroke, Anja (British Journal of Nutrition)

A comparative evaluation of two different approaches to estimating age at adiposity rebound - Kroke, A; Hahn, S; Buyken, Anette; Liese, A D (International Journal of Obesity)

Neue Orientierungen der Ernährungs- und Verbraucherbildung - Schlegel-Matthies, Kirsten (Aktuelle Aspekte in der Ernährungsbildung und -beratung. Tagungsband der DGE-Arbeitstagung am 29. und 30. September in Paderborn)

Ernährungs- und Verbraucherbildung in der Reform - Schlegel-Matthies, Kirsten (Pisa“ in der Verbraucherbildung. Sind wir alle Konsum-Analphabeten?)

Fachdidaktische Perspektiven auf den Umgang mit Heterogenität im haushaltsbezogenen Unterricht - Schlegel-Matthies, Kirsten (Heterogenität als Chance. Vom produktiven Umgang mit Gleichheit und Differenz in der Schule.)

Zwischen Selbstbestimmung und Verantwortung – Herausforderungen für Verbraucherbildung - Schlegel-Matthies, Kirsten (Haushalt & Bildung)

Verbraucherbildung vor neuen Herausforderungen. Editorial - Schlegel-Matthies, Kirsten (Haushalt & Bildung)

Virtual and augmented reality support for discrete manufacturing system simulation - Dangelmaier, Wilhelm; Fischer, Matthias; Gausemeier, Jürgen; Grafe, Michael; Matysczok, Carsten; Mueck, Bengt (Computers in Industry)
Nowadays companies operate in a difficult environment: the dynamics of innovations increase and product life cycles become shorter. Furthermore products and the corresponding manufacturing processes get more and more complex. Therefore, companies need new methods for the planning of manufacturing systems. One promising approach in this context is digital factory/virtual productionthe modeling and analysis of computer models of the planned factory with the objective to reduce time and costs. For the modeling and analysis various simulation methods and programs have been developed. They are a highly valuable support for planning and visualizing the manufacturing system. But there is one major disadvantage: only experienced and long trained experts are able to operate with these programs. The graphical user interface is very complex and not intuitive to use. This results in an extensive and error-prone modeling of complex simulation models and a time-consuming interpretation of the simulation results. To overcome these weak points, intuitive and understandable manmachine interfaces like augmented and virtual reality can be used. This paper describes the architecture of a system which uses the technologies of augmented and virtual reality to support the planning process of complex manufacturing systems. The proposed system assists the user in modeling, the validation of the simulation model, and the subsequent optimization of the production system. A general application of the VR- and AR-technologies and of the simulation is realized by the development of appropriate linking and integration mechanisms. For the visualization of the arising 3D-data within the VR- and AR-environments, a dedicated 3D-rendering library is used.

Multi-User Support and Motion Planning of Humans and Humans Driven Vehicles in Interactive 3D Material Flow Simulations - Fischer, Matthias; Mueck, B.; Mahajan, K.; Kortenjan, M.; Laroque, C.; Dangelmaier, W. (Proceedings of the Winter Simulation Conference)

Online Occlusion Culling - Frahling, Gereon; Krokowski, Jens (Proc. of the 13th Annual European Symposium on Algorithms (ESA 2005))
Modern computer graphics systems are able to render sophisticated 3D szenes consisting of millions of polygons. In this paper we address the problem of occlusion culling. Aila, Miettinen, and Nordlund suggested to implement a FIFO buffer on graphics cards which is able to delay the polygons before drawing them. When one of the polygons within the buffer is occluded or masked by another polygon arriving later from the application, the rendering engine can drop the occluded one without rendering, saving important rendering time. We introduce a theoretical online model to analyse these problems in theory using competitive analysis. For different cost measures addressed we invent the first competitive algorithms for online occlusion culling. Our implementation shows that these algorithms outperform known ones for real 3D scenes as well.

Methods to lead the user to significant processes in a 3D material flow simulation - Dangelmaier, Wilhelm; Mueck, Bengt; Fischer, Matthias; Mahajan, Kiran; Laroque, Christoph (Simulation in wider Europe - 19th European Conference on Modelling and Simulation ECMS 2005)

Ernährung zwischen Natur und Kultur: Das Beispiel Fleisch - Schlegel-Matthies, Kirsten (Neue Aspekte der Ernährungsbildung)

Neues Konsum- und Finanzmanagement - Schlegel-Matthies, Kirsten (Neue Hauswirtschaft. Ein Material für Multiplikator/innen der familien- und haushaltsbezogenen Bildung)

Kooperationsprojekt REVIS: Länderbericht Baden-Württemberg. - Methfessel, B.; Bigga, Regine (Schlussbericht, REVIS – Reform der Ernährungs- und Verbraucherbildung in Schulen.)

Bildungsstandards. Eine Diskussion um Arbeitslehre - Haushalt - Technik - Textilarbeit - Wirtschaft - Bigga, Regine

Differences between recumbent length and stature measurement in groups of 2- and 3-y-old children and its relevance for the use of European body mass index references - Buyken, Anette; Hahn, S; Kroke, A (International Journal of Obesity)

Verbraucherbildung im Forschungsprojekt REVIS – Grundlagen - Schlegel-Matthies, Kirsten

„Was gibt’s heute?“ Aktuelle Ansätze der Ernährungsbildung - Schlegel-Matthies, Kirsten (Campus Culinaire)

Guidance of Users in Interactive 3D-Visualisations of Material Flow Simulations - Mueck, Bengt; Dangelmaier, Wilhelm; Laroque, Christoph; Fischer, Matthias; Kortenjan, Michael (Simulation and Visualisation 2004)
The visualisation of manufacturing-processes assists the user in understanding and analysis. Typically he can move free and unguided in a virtual environment which visualizes the entire process. Thus knowledge and conclusions are to some extend acquired on a random base. This article describes the development of a tool, which enables the user to interactively improve significant production processes in the simulation. He moves in a virtual 3D-environment (walkthrough system) and is able to acquire automatically calculated indications for significant processes. At the same time the simulation considers significant objects in a more detailed way. If the viewer is interested in a significant process, he is automatically guided to the relevant location where he can examine the critical situation by modification of the simulation model.

Research Challenges in Mobility and Moving Networks: An Ambient Networks View - Typpö, Ville; Eisl, Jochen; Höller, Jan; Agüero, Ramon; Karl, Holger (Broadband Satellite Comunication Systems and the Challenges of Mobility - IFIP TC6 Workshops on Broadband Satellite Communication Systems and Challenges of Mobility, World Computer Congress, August 22-27, 2004, Toulouse, France)

openVisaar: Enriching Cooperative Visualization by Combining Open Technologies - Goetz, Frank; Domik, Gitta (Cooperative Design, Visualization, and Engineering, First International Conference, (CDVE) 2004, Palma de Mallorca, Spain, September 19-22, 2004, Proceedings)

An XML-based visual shading language for vertex and fragment shaders - Goetz, Frank; Borau, Ralf; Domik, Gitta (Proceeding of the Ninth International Conference on 3D Web Technology, Web3D 2004, Monterey, California, USA, April 5-8, 2004)

Sundholm, Göran. “Frege, August Bebel and the Return of Alsace-Lorraine: The Dating of the Distinction between Sinn and Bedeutung”, In: History and Philosophy of Logic 22 (2001), 57–73 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Klement, Kevin C., “Russell’s Paradox in Appendix B of the Principles of Mathematics: Was Frege’s response adequate?”, In: History and Philosophy of Logic 22 (2001), 13-28 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

„Liebe geht durch den Magen“: Mahlzeit und Familienglück im Strom der Zeit - Schlegel-Matthies, Kirsten (Die Revolution am Esstisch. Neue Studien zur Nahrungskultur im 19./20. Jahrhundert)

Bildung für Lebensführung – eine neue Aufgabe für die Schule?! - Schlegel-Matthies, Kirsten (Fokus Haushalt. Beiträge zur Sozioökonomie des Haushalts)

Fast Relative Approximation of Potential Fields - Ziegler, Martin (Lecture Notes in Computer Science)
Multi-evaluation of the Coulomb potential induced by N particles is a central part of N-body simulations. In 3D, known subquadratic time algorithms return approximations up to given ABSOLUTE precision. By combining data structures from Computational Geometry with fast polynomial arithmetic, the present work obtains approximations of prescribable RELATIVE error e>0 in time O(1/e*N*polylog N).

Komponenten zur aktiven Unterstützung der Analyse von Materialflusssimulationen in virtuellen Umgebungen - Dangelmaier, Wilhelm; Franke, Werner; Mueck, Bengt; Fischer, Matthias (2. Paderborner Workshop Augmented & Virtual Reality in der Produktentstehung)
Simulation und Visualisierung sind anerkannte Mittel zum Verstehen und Analysieren von Fertigungsprozessen. In Visualisierungen von Fertigungsprozessen können Betrachter frei und ungeleitet umherwandern. Erkenntnisse werden so aber eher zufällig erworben. Dieser Artikel skizziert ein System und Methoden, die den Betrachter unterstützen auf auffällige/signifikante Prozesse/ Punkte in Materialflusssimulationen aufmerksam zu werden und diese zu entschärfen. Es wird der Entwurf eines Werkzeugs beschrieben, dass den Betrachter einer Simulation die Möglichkeit bietet, signifikante Produktionsprozesse interaktiv zu verbessern. Der Benutzer wird sich in einer virtuellen 3D-Umgebung (Walkthrough-System) bewegen können und automatisch ermittelte Indizien für signifikante Abläufe erhalten. Zugleich soll die Simulation signifikante Objekte genauer simulieren. Bekundet der Benutzer Interesse an einem signifikanten Prozess, wird er automatisch zu dem jeweiligen Ort geführt werden und dort durch Eingriffe in die Simulation die kritische Situation experimentell untersuchen können. Da der kritische Moment in der Vergangenheit liegt und somit vom Betrachter schon verpasst ist, wird es dem Betrachter möglich sein, die Simulation auf einen Zeitpunkt vor dem Eintreten zurück zu setzen. Die virtuelle Szene (3D-Grafik-Modelle) einer typischen dynamischen Simulationsumgebung ist in der Regel zu komplex, um sie in Echtzeit in einem Walkthrough-System zu visualisieren und darzustellen. Typischerweise werden Approximationsverfahren eingesetzt, um die Komplexität zu reduzieren und ein flüssiges Navigieren des Betrachters zu erlauben. Durch spezifische Simulations-Anforderungen ist bekannt, an welchen Objekten des Simulationsmodells Probleme auftreten; sie sind für den Betrachter wichtig. Die zugehörigen virtuellen 3D-Repräsentanten, können von den Approximationsalgorithmen mit einer besonders hohen Darstellungsqualität dargestellt werden und die übrigen Teile der virtuellen Szene entsprechend vernachlässigt werden. Solche Approximationsalgorithmen und Datenstrukturen nutzen die spezifischen Eigenschaften virtueller Simulationsumgebungen aus, um eine hohe Darstellungsqualität und Darstellungsperformance zu erreichen.

Planung von komplexen Fertigungssystemen durch Einsatz einer VR/AR-unterstützten Simulation - Fischer, Matthias; Grafe, Michael; Matysczok, Carsten; Schoo, Michael; Mueck, Bengt (2. Paderborner Workshop Augmented & Virtual Reality in der Produktentstehung)
In der heutigen Zeit operieren Unternehmen zunehmend in einem schwierigen Umfeld: Die Innovationsdynamik nimmt zu und die Produktlebenszyklen werden kürzer. Daraus resultieren hohe Anforderungen an die Planung von Fertigungssysteme. Um diesen Prozess zu unterstützen, sollen die Technologien Augmented Reality und Virtual Reality in einem integrierten System genutzt werden. Dieses System unterstützt den Anwender bei der Modellbildung, der Validierung des Simulationsmodells sowie der folgenden Optimierung des Fertigungssystems. Durch die Entwicklung geeigneter Kopplungs- bzw. Integrationsmechanismen wird eine durchgängige Nutzung der Technologien AR, VR und Simulation realisiert. Die Visualisierung der anfallenden 3D-Daten innerhalb der VR- und ARUmgebungen erfolgt mittels einer 3D-Renderinglibrary, die es durch den Einsatz von neuen entwickelten Verfahren ermöglicht, die verwendeten 3D-Modelle weitgehend automatisiert aus unternehmensinternen 3D-CAD-Modellen zu generieren.

A Framework for Video-based and Hardware-Accelerated Remote 3D-Visualization - Goetz, Frank; Domik, Gitta (Eurographics 2003 - Short Presentations)

Online Marktforschung im Mittelstand: Analyse von Konsumentenverhalten in 3D-Internet-Welten - Schryen, Guido; Herstell, Jan; Schoenen, Markus

3D interaktives Baukastensystem unter Verwendung von Augmented Reality Techniken - Schwerdtfeger, Bj{\; Goetz, F; Domik, Gitta

Schirn, Matthias/Niebergall, Karl-Georg, “Extensions of the Finitist Point of View”, In: History and Philosophy of Logic 22 (2001), 135–161 - Peckhaus, Volker (Mathematical Reviews)

Lernen mit allen Sinnen – Lernen an vielen Orten. Tradition und Möglichkeiten des Lernens an verschiedenen Lernorten - Bigga, Regine (Haushalt & Bildung)

Vorsorgendes Haushalten: Computergestützte Bewertung von Lebensmittelverarbeitung und Lebensmittelqualität - Bigga, Regine; Schack, Pirjo Susanne (Schule zwischen materieller und virtueller Lernkultur)

Electronic transport in a one-dimensional random array of scatterers - Meier, Torsten; Filinov, V.S.; Thomas, P.; Varga, I.; Bonitz, M.; Fortov, V.E; Koch, S.W. (Journal of Physics A: Mathematical and General)
The quantum dynamics of an ensemble of interacting electrons in an array of random scatterers is treated using a new numerical approach for the calculation of average values of quantum operators and time correlation functions in the Wigner representation. This approach combines both molecular dynamics and Monte Carlo methods and computes numerical traces and spectra of the relevant dynamical quantities such as momentum–momentum correlation functions and spatial dispersions. Considering, as an application, a system with fixed scatterers, the results clearly demonstrate that the many-particle interaction between the electrons can lead to an enhancement of the conductivity at intermediate densities.

Realtime Navigation in Highly Complex 3D-Scenes Using JPEG Compression - Klein, Jan; Krokowski, Jens; Cuntz, Nicolas (Proc. of 4. GI-Informatiktage)
We present a new and easy to use framework for navigating through scenes of arbitrary complexity and topology. In the preprocessing, images for discrete viewpoints and viewing directions are rendered and stored on an external volume. During navigation each image can be displayed within a very short time by loading it from the volume. For acceleration, our prefetching strategy loads possibly needed images for the next few frames if the viewer takes a break. The measurements show that we achieve interactive frame rates, whereby the difference between the minimal and maximal display time is very small. Our system works well with scenes modelled by polygons, but also digital photos can easily be used for describing a 3D scene.

Checking Behavioural Subtypes via Refinement - Wehrheim, Heike (Formal Methods for Open Object-Based Distributed Systems V, IFIP {TC6/WG6.1} Fifth International Conference on Formal Methods for Open Object-Based Distributed Systems {(FMOODS} 2002), March 20-22, 2002, Enschede, The Netherlands)

Protein intake and urinary albumin excretion rates in the EURODIAB IDDM Complications Study - Toeller, M.; Buyken, Anette; Heitkamp, G.; Brämswig, S.; Mann, J.; Milne, R.; Gries, F. A.; Keen, H. (Diabetologia)

Relation of fibre intake to HbA 1c and the prevalence of severe ketoacidosis and severe hypoglycaemia - Buyken, Anette; Toeller, M.; Heitkamp, G.; Vitelli, F.; Stehle, P.; Scherbaum, W. A.; Fuller, J. H. (Diabetologia)

Carbohydrate sources and glycaemic control in Type 1 diabetes mellitus - Buyken, Anette; Toeller, M.; Heitkamp, G.; Irsigler, K.; Holler, C.; Santeusanio, F.; Stehle, P.; Fuller, J. H.; Group, the Eurodiab Iddm Complications Stu (Diabetic Medicine)

The Impact of Dietary Fat Composition on Serum Leptin Concentrations in Healthy Nonobese Men and Women - Kratz, Mario; von Eckardstein, Arnold; Fobker, Manfred; Buyken, Anette; Posny, Nicole; Schulte, Helmut; Assmann, Gerd; Wahrburg, Ursel (The Journal of Clinical Endocrinology & Metabolism)

Protein intake - new evidence for its role in diabetic nephropathy - Toeller, M; Buyken, Anette (Nephrology Dialysis Transplantation)

Das Modell der Salutogenese als Handlungsanleitung für haushaltsbezogene Bildung? Fragen und Folgerungen - Schlegel-Matthies, Kirsten (Haushalt & Bildung)

O Laboratório de Fontes Alternativas de Energia da UFRJ – LAFAE (Labor für alternative Energiequellen an der UFRJ) - Rosa, L. P.; Krauter, Stefan; Nascimento, J. L.; Sampaio, M.; Silva, N. F.; Araújo, M. P.; Petersen, R. C. (IX Congresso Brasileiro de Energia, Rio de Janeiro (Brasilien), 21.–22. Mai 2002, Band 4, S. 1780–1785.)

Data Warehouse in der Marktforschung - Analyse von Benutzeraktivitäten in virtuellen Welten - Schryen, Guido; Schoenen, Markus (Data Warehousing 2002)
Bei der Online-Marktforschung lässt sich mit Hilfe virtueller 3D-Welten das Konsumentenverhalten beobachten. Da die Struktur der dabei anfallenden Daten multidimensional ist und die marktforschungsrelevanten Anfragen eine hohe OLAP-Affinität aufweisen, wurde hierzu im Rahmen des Forschungsprojekts Benevit ein Data Warehouse konzipiert und realisiert. Im Rahmen einer Standardisierung der Protokollierung von Konsumentenaktivitäten und deren prototypischen Realisierung erwies sich der Data Warehouse/OLAP-Ansatz zur Speicherung, Analyse und Präsentation der Marktforschungsdaten als adäquates Instrumentenbündel.

x3Dogl: ein auf XML basierendes Web3D-System zur Darstellung interaktiver 3D-Szenen - Goetz, F.; Domik, Gitta (Informatiktage 2002)

Darstellung und Bewertung von Online und Offline Medien unter dem Gesichtspunkt nachhaltiger Ernährungsstile. Lehren und Lernen im haushaltsbezogenen Unterricht. - Bigga, Regine; Schack, Pirjo Susanne (Haushalt & Bildung)

A UML Profile for Real-Time Constraints with the OCL - Flake, Stephan; Müller, Wolfgang (Proceedings of the UML 2002 - The Unified Modeling Language)
This article presents a UML profile for an OCL extension that enables modelers to specify behavioral, state-oriented real-time constraints in OCL. In order to perform a seamless integration into the upcoming UML2.0 standard, we take the latest OCL2.0 metamodel proposal by Warmer et al. [22] as a basis. A formal semantics of our temporal OCL extension is given by a mapping to time-annotated temporal logics formulae. To give an example of the applicability of our extension, we consider a modeling approach for manufacturing systems called MFERT. We present a corresponding UML profile for that approach and combine both profiles for formal verification by real-time model checking.

Der Technikbegriff bei Rosa Luxemburg und seine Bedeutung für aktuelle techniksoziologische Fragen (Rosa Luxemburg’s Notion of Technology and Its Implications for Sociology of Technology) - Fuchs, Christian (Vorschein 22/23)

Nutrient intakes as predictors of body weight in European people with type 1 diabetes. - Toeller, M; Buyken, Anette; Heitkamp, G; Cathelineau, G; Ferriss, B; Michel, G; IDDM Complications Study Group, EURODIAB (Int J Obes Relat Metab Disord)

Glycemic index in the diet of European outpatients with type 1 diabetes: relations to glycated hemoglobin and serum lipids. - Buyken, Anette; Toeller, M; Heitkamp, G; Karamanos, B; Rottiers, R; Muggeo, M; Fuller, JH; IDDM Complications Study Group, EURODIAB (Am J Clin Nutr)

Salutogenese und haushaltsbezogene Bildung – didaktische Folgerungen - Schlegel-Matthies, Kirsten (Salutogenese und Ernährungsbildung. Abstracts des Workshops vom 9. und 10. März 2001)

Lebensstile von Jugendlichen und Umgang mit Geld. Folgerungen für haushaltsbezogene Bildung - Schlegel-Matthies, Kirsten (Haushalt & Bildung)

Factoring a binary polynomial of degree over one million - Bonorden, Olaf; von zur Gathen, Joachim; Gerhard, Jürgen; Müller, Olaf (ACM SIGSAM Bulletin)
On 22 May 2000, the factorization of a pseudorandom polynomial of degree 1 048 543 over the binary field Z 2 was completed on a 4-processor Linux PC, using roughly 100 CPU-hours. The basic approach is a combination of the factorization software BIPOLAR and a parallel version of Cantor's multiplication algorithm. The PUB-library (Paderborn University BSP library) is used for the implementation of the parallel communication.

Occlusion Culling for Virtual Environments based on the 3D-Sectorgraph - Klein, Jan; Fischer, Matthias (Proc. of 3. GI-Informatiktage 2001)
We present a new approximate occlusion-culling algorithm that in contrast to other algorithms, manages the objects of the scene in a 3D-sectorgraph. For generating a frame, as far as possible only the visible objects are rendered that can be found quickly by an edge of the graph. The algorithm allows a real-time navigation with over 20 frames per second in complex scenes consisting of over 10 millions of polygons. Moreover, approximation errors are very low.

Satellite Monitoring of Remote PV-Systems - Krauter, Stefan; Ochs, F.; Depping, T. (Proceedings of the 17th European Photovoltaic Solar Energy Conference and Exhibition, München (Deutschland), 22.–26. Oktober 2001, Band 3, S. 2598–2599)

Development of an All-in-one Solar Home System - Ochs, F.; Krauter, Stefan (Proceedings of the 17th European Photovoltaic Solar Energy Conference and Exhibition, München (Deutschland), 22.–26. Oktober 2001, Band 3, S. 2595–2597)

Jugend ohne ARBEITsLEHRE? Bilanz und Perspektiven schulischer Berufsorientierung. - Bigga, Regine (Arbeitslehre 2001. Bilanzen - Initiativen - Perspektiven.)

Customer-Oriented Systems Design through Virtual Prototyps - Flake, Stephan; Geiger, Christian; Müller, Wolfgang; Ruf, Jürgen (Proceedings of IEEE KMN 2001)
Rapid prototyping based on 3D models is well accepted for several applications. This article addresses the application of animated virtual 3D prototypes for the development of computer-based systems supporting early collaboration of the system designer with the external customer. Our methodology seamlessly integrates illustration through 3D animation with the main tasks of computer-based real-time systems development, i.e., implementation and verification. The approach is outlined by the example of the design of a flexible manufacturing system.
Keywords: Virtual prototyping; Animation; Collaboration; System analysis and design; Feedback; Application software; Power system modeling; Handicapped aids; Process design; Contracts

Carbohydrate sources and glycaemic control in Type 1 diabetes mellitus. EURODIAB IDDM Complications Study Group. - Buyken, Anette; Toeller, M; Heitkamp, G; Irsigler, K; Holler, C; Santeusanio, F; Stehle, P; Fuller, JH (Diabet Med)

Developing Effective Navigation Techniques in Virtual 3D Environments - Volbracht, Sabine; Domik, Gitta (Virtual Environments 2000)

Optimization of Interblade Friction Damper - Panning, Lars; Sextro, Walter; Popp, Karl (International Gas Turbine & Aeroengine Congress & Exhibition, ASME)
the vibration amplitudes of bladed disk assemblies can be reduced significantly by means of friction damping devices such as shrouds, damping wires and interblade Friction dampers. in practice, interblade Friction dampers are applied in rotating arrangements with various geometries showing curved or flat surfaces like so-called wedge-shaped dampers. this paper is focusing on a computation method to predict the dynamical behaviour of turbine blades with Friction dampers including both, curved and wedge-shaped dampers with hertzian and non-herutian contact conditions, respectively. the presented computation method uses a 3d contact model to calculate the contact forces, including normal and tangential stiffnesses, roughness and microslip effects. the relative displacements in the contact area can be expressed by means of 6 dof of the blade platforms and 6 rigid body dof of the damper including translational and rotational displacements. the relative displacement of the Friction damper with respect to the adjacent blades can be derived from the contact kinematics of the blade-damper-blade system and the equations of motion of the Friction damper. thus, the model can be applied to investigate spatial motions of the bladed disk assembly including bending and torsional vibrations. a comparison of different Friction damper designs with respect to an optimal damper geometry and damper mass is presented. the advantages and disadvantages of each design will be discussed. experimental results are shown to validate the developed computation method.

Fünf vor zwölf und keinen Ausbildungsplatz. Eine Unterrichtsskizze zur Berufsorientierung. - Bigga, Regine (awt-info)

Prototyping einer Fahrzeug-steuerung in einer virtuellen 3D-Umgebung - Braatz, A.; Flake, Stephan; Müller, Wolfgang; Westkämper, E.
Prototyping mit 3D-Modellen in virtueller Umgebung ist eine kostengünstige Alternative zur Entwicklung von physikalischen Modellen und Mock-ups. Für einige Anwendungen ergeben sich erhebliche Vorteile durch die Validierung in einer virtuellen Umgebung. In diesem Artikel stellen wir den Einsatz einer 3D-Animation zur Entwicklung und zum Test einer Fahrzeugsteuerung vor. Basierend auf dem Prinzip der schrittweisen Verfeinerung kann die Steuerung zunächst nur unter Berücksichtigung der Kommunikation zwischen den Basiskomponenten entworfen werden. Im zweiten Schritt wird die Ansteuerung der Aktoren unter Auswertung der Sensoren berücksichtigt. Letztendlich ist das System unter Einflussnahme der physikalischen Größen zu validieren. Wir stellen die Schnittstelle exemplarisch anhand einer Steuerung für fahrerlose Transportfahrzeuge im Szenario eines holonischen Transportsystems vor.

Prevalence of chronic complications, metabolic control and nutritional intake in type 1 diabetes: comparison between different European regions. EURODIAB Complications Study group. - Toeller, M; Buyken, Anette; Heitkamp, G; Berg, G; Scherbaum, WA (Horm Metab Res)

Fiber intake, serum cholesterol levels, and cardiovascular disease in European individuals with type 1 diabetes. EURODIAB IDDM Complications Study Group. - Toeller, M; Buyken, Anette; Heitkamp, G; de Pergola, G; Giorgino, F; Fuller, JH (Diabetes Care)

Interkulturelle Bildung als Aufgabe haushaltsbezogenen Unterrichts - Schlegel-Matthies, Kirsten (Internationale Perspektiven in Hauswirtschaft und Haushaltswissenschaft. 20 Jahre Beirat. Dokumentations- und Diskussionsbeiträge)

Virtuelles Prototyping einer Robotersteuerung durch interaktive 3D-Simulation - Geiger, Christian; Lehrenfeld, G.; Müller, Wolfgang

Visual Specification, Modeling, and Illustrations of Complex Systems - Geiger, Christian; Lehrenfeld, G.; Müller, Wolfgang (Proceedings of HICSS-32)
This article introduces and discusses different innovative means for visual specification and animation of complex concurrent systems. It introduces the completely visual programming language Pictorial Janus (PJ) and its application in the customer-oriented design process. PJ implements a completely visual programming language with inherent animation facilities. The article outlines the transformation of purely visual PJ programs into textual imperative programming languages. The second part of the article investigates animated 3D-presentations and introduces a novel approach to an animated 3D programming language for interactive customer-oriented illustrations.
Keywords: Animation; Computer languages; Object oriented modeling; Collaboration; Process design; Graphical user interfaces; Jacobian matrices; Standardization; Feedback; Software prototyping

Scalable System for 3D Audio Raytracing - Müller, Wolfgang; Ullmann, F. (Proceedings IEEE International Conference on Multimedia Computing and Systems)
Though several approaches in sound processing are denoted as 3D audio very few of them generate high quality 3D audio information which allows listeners to exactly locate sound sources in three dimensional space. We present an approach to enhance sound by high quality 3D audio information through acoustic ray tracing where 3D audio is offline processed with digital filters of a head-related transfer function. The basic approach computes a fixed sound source for fixed listener. This approach is extended to generate 3D audio for moving listeners in interactive environments.
Keywords: Ray tracing; Loudspeakers; Motion pictures; Acoustic reflection; Ear; Digital filters; Parallel processing; Humans; Physics; Crosstalk

Relation of fibre intake to HbA1c and the prevalence of severe ketoacidosis and severe hypoglycaemia. EURODIAB IDDM Complications Study Group. - Buyken, Anette; Toeller, M; Heitkamp, G; Vitelli, F; Stehle, P; Scherbaum, WA; Fuller, JH (Diabetologia)

An Example of Task Oriented Empirical Evaluations of 3D-Display Modes - Volbracht, Sabine; Domik, Gitta; Shahrbabaki, Khatoun; Fels, Gregor (Journal of Universal Computer Science)

Beller, Walter, “Logic in Mexico”, In: Santiago Ramirez (ed.), Mexican Studies in the History and Philosophy of Science, Kluwer: Dordrecht 1995 (= Boston Stud. Philos. Sci.; 172), 1–22 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Berufsorientierung in Zeiten der Krise: Thematisierung - Dethematisierung. - Bigga, Regine (Schule und Arbeitswelt. Zwischen Thematisierung und De-Thematisierung von Geschlecht.)

Anregungen für die Lehrplanarbeit hinsichtlich der Gleichstellung der Geschlechter. Lehrpläne für Mädchen und Jungen. - Bigga, Regine (Lisa-Jahrbuch)

Authoring Communicating Agents in Virtual Environments - Geiger, Christian; Lehrenfeld, Georg; Müller, Wolfgang (Proceedings of the Annual Conference for the Computer Human Interaction)
3D-graphics popularity has steadily increased in a number of areas such as entertainment, scienti c vi- sualization, simulation, and virtual reality. Despite this rapid growth the authoring of animated 3D objects in virtual environments is stil l by no means trivial. This article presents new concepts of the animated 3D programming language SAM (Solid Agents in Motion) and its programming environment. In SAM, the main syntactic objects like agents, rules, and messages are represented as 3D objects. The design of a SAM pro- gram is supported by a dedicated 3D structure editor. The editor al lows the de nition and spatial arrange- ment of SAM agents in a 3D scene by direct manipu- lation. The paper gives a number of SAM examples, demonstrating the authoring of simple animated vir- tual 3D scenarios.

SAM - An Animated 3D Programming Language - Geiger, Christian; Müller, Wolfgang; Rosenbach, W. (Proceedings of the IEEE Symposium on Visual Languages)
This article presents the animated visual 3D programming language SAM (Solid Agents in Motion) for parallel systems specification and animation. A SAM program is a set of interacting agents synchronously exchanging messages. The agent's behaviour is specified by means of production rules with a condition and a sequence of actions each. Actions are linearly ordered and execute when matching a rule. In SAM, main syntactic objects like agents, rules, and messages are 3D. These objects can have an abstract and a concrete, solid 3D presentation. While the abstract representation is for programming and debugging, the concrete representation is for animated 3D end-user presentations. After outlining the concepts of SAM this article gives two programming examples of 3D micro worlds and an overview of the programming environment.
Keywords: Animation; Computer languages; Solids; Concrete; Application software; Virtual reality; Programming profession; Switches; Visualization; Debugging

Repeatability of three-day dietary records in the EURODIAB IDDM Complications Study. - Toeller, M; Buyken, Anette; Heitkamp, G; Milne, R; Klischan, A; Gries, FA (Eur J Clin Nutr)

Logik, Mathesis universalis und allgemeine Wissenschaft. Leibniz und die Wiederentdeckung der formalen Logik im 19. Jahrhundert - Peckhaus, Volker
Rezensionen: J. Legris, “Mathesis Universalis”, Mathesis 13 (1997), 167– 175; Zbl. Math. 884.01021 (R. Murawski); Philosophischer Literaturanzeiger 51 (1998), 114–117 (G. Schenk); MR 98h:01013 (H. Sinaceur); Peirce Project Newsletter 3 No. 1, 7; Philosophiegeschichte und logische Analyse. Logical Analysis and History of Philosophy, Bd. 2, Mentis: Paderborn 1999, 259–264 (W. Malzkorn); History and Philosophy of Logic 20 (1999), 67–69 (H. Linneweber-Lammerskitten); Erkenntnis 50 (1999), 133–136 (P. Mancosu); Berichte zur Wissenschaftsgeschichte 22 (1999), 207–208 (P. Mancosu); NTM. Schriftenreihe für Geschichte der Naturwissenschaften, Technik und Medizin N.S. 8 (2000), H. 1, 290 (K.-H. Schlote), 49–50; Anuario Filosofico 32 (1999), 853–854; M.F., “La logica di Leibniz nel XIX secolo”, Giornale critico della filosofia Italiana 6 ser. 20 (2000), 161–164; Archiv für Geschichte der Philosophie 82 (2000), 349–352 (R. Vilkko); Epistemologia 24 (2001), 152–155 (M. Ferriani); The Review of Modern Logic 9, nos. 3 & 4 (2003–2004), 119–122 (H. Frank).

Rademacher, Ulf: Der Europäische Betriebsrat. Die Richtlinie 94 / 45 / EG des Rates vom 22. 4. 1994 und ihre Umsetzung in nationales Recht; Nomos: Universitätsschriften Recht 1997 - Krimphove, Dieter (Recht der Arbeit (RdA))

How effective are 3D display modes? - Volbracht, Sabine; Domik, Gitta; Shahrbabaki, Khatoun; Fels, Gregor (Proceedings of the ACM SIGCHI Conference on Human factors in computing systems)

Blinde Flecken in der Berufsorientierung im Rahmen der Arbeitslehre. Zusammenhang von Erwerbsarbeit und Hausarbeit fehlt nach wie vor. - Bigga, Regine (Hauswirtschaftliche Bildung)

Visual-Textual Prototyping of 4D Scenes - Dücker, M.; Geiger, Christian; Hunstock, R.; Lehrenfeld, Georg; Müller, Wolfgang (Proceedings of the 1997 IEEE Symposium on Visual Languages)
3D-graphics are becoming popular in a steadily increasing number of areas such as entertainment, scientific visualization, simulation, and virtual reality. Despite this rapid growth the generation of animated 3D scenes is by no means trivial. Since animated 3D objects evolve over time the authors denote these objects as 4D. The article presents a novel approach to the rapid prototyping of 4D models. They introduce the AAL (Animated Agent Layer) system. AAL is an interpreter-based approach covering a textual (AAL-PR) as well as a visual command language (AAL-VL) for the specification of the dynamics in 4D scenes. AAL provides support for different levels of abstraction: primitives, structured objects, animated objects, and animated (autonomous) agents.
Keywords: Prototypes; Layout; Animation; Command languages; Application software; Libraries; Virtual reality; Computer graphics; Hardware; Context modeling

Nutritional intake of 2868 IDDM patients from 30 centres in Europe. EURODIAB IDDM Complications Study Group. - Toeller, M; Klischan, A; Heitkamp, G; Schumacher, W; Milne, R; Buyken, Anette; Karamanos, B; Gries, FA (Diabetologia)

An Experimental Comparison of 3D Display Modes - Volbracht, S.; Domik, Gitta; Shahrbabaki, K.; Fels, G. (Proceedings of IEEE Visualization)

3d core-level shifts at - Schmidt, Wolf Gero; Käckell, P.; Bechstedt, F. (Surface Science)

Se-induced 3d core-level shifts of GaAs(110) - Käckell, Peter; Schmidt, Wolf Gero; Bechstedt, Friedhelm (Applied Surface Science)